An investigation of the level and determinants of financial literacy among different groups in Sabah - Lim, Thien Sang; Zatul Karamah A.B.U.; Rasid Mail; Amer Azlan Abdul Jamal; Zaiton Osman; Rosle Mohidin (Universiti Malaysia Sabah, 2014)
In Sabah and the rest Malaysia, there are increasing signs of personal financial mismanagement and financial stress, especially among the young generation. Experts in the area of personal finance posit that financial illiteracy is one of the contributing factors to the inability of a person to properly manage his or her financial matters as well as longterm financial commitment. Sabah, being one of the biggest and one of the diverse states has many preconditions for financial literacy research. The result of the research indicates the level of financial literacy in Sabah is very low. Based on the sample of size of 1191 from across the state, the mean of individual's score is 9.6 (based on maximum scale of 24) and almost 70 percent (69.8% to be exact) of the respondents fail in the literacy test. Analysis based on demographical factors suggests that males are better financial literacy than females. Financial literacy is also better among the higher age groups. Financial literacy gaps also exist in term of level of education and income group. This study also finds that geographical location is important factor. Perhaps the most interesting factor of the research of that a non-majority ethnic group has came up top in financial literacy, and the performance gap compare to all other ethnic groups is statistically significant. Last but not least, the researchers call for more financial education programmes that are aimed to inculcate positive attitude towards financial management in order to create a more positive financial behaviour among people. This call is made based on a series of bivariate relationship analyses that were conducted in the research.